MODAL SOSIAL PEDAGANG KELILING PASAR TRADISIONAL (Studi Kasus Pedagang Pakaian Asal Desa Air Buluh Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi) - Lisa Putri Yayanda; Teguh Widodo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Clothing traders traveling to traditional markets from Air Buluh Village, Kuantan Mudik District, Kuantan Singingi Regency have been clothing traders for many years, and still survive as clothing traders who trade around the markets, this is certainly inseparable from capital. social they have. This research was conducted in Air Buluh Village, Kuantan Mudik District, Kuantan Singingi Regency with the aim of knowing the social capital owned by clothing traders traveling around traditional markets. The method used in this research is descriptive qualitative method. Subjects taken in this study consisted of 10 people. This study uses the theory of social capital which consists of social networks, social norms, and trust. The results obtained in this study that social capital is very important in maintaining the sustainability of the business of clothing traders around traditional markets and providing convenience and smooth running of business such as the existence of a network that helps facilitate the running of this business. The existence of social norms that are run by them makes everything more organized and directed. Trust strengthens the relationship between traders and agents, traders with buyers and between fellow traders which then leads to the sustainability of these relationships.  Keywords: Social Capital, Mobile Clothing Traders, Traditional Markets